Cytotype distribution patterns, ecological differentiation, and genetic structure in a diploid–tetraploid contact zone of Cardamine amara. Issue 8 (1st August 2015) - Zozomová‐Lihová, Judita; Malánová‐Krásná, Iva; Vít, Petr; Urfus, Tomáš; Senko, Dušan; Svitok, Marek; Kempa, Matúš; Marhold, Karol
Abstract : Premise of the study: Contact zones between diploids and their autopolyploid descendants represent a unique evolutionary venue for studying polyploid establishment, cytotype coexistence, and interactions. Here, we examine cytotype coexistence in a diploid–tetraploid contact zone of a perennial herb, Cardamine amara, located north of the Alps by assessing cytotype spatial patterns, ecological divergence, and genetic variation and structure. Methods: Flow cytometry was applied to screen DNA ploidy levels in 302 populations (3296 individuals) and the genetic variation of a selection of 25 populations was examined using microsatellite and AFLP markers. Environmental (landscape and climatic) data were analyzed to assess ecological differentiation between the cytotypes. Key results: A parapatric distribution of the cytotypes with a relatively wide (over 100 km in some regions) secondary contact zone was identified. Mixed‐ploidy populations, documented for the first time in this species, as well as triploid individuals were found along the diploid–tetraploid borderline. Different climatic requirements of the two main cytotypes were revealed, mirrored in their altitudinal separation. The tetraploids were genetically differentiated from both the diploids and the modeled, in silico autotetraploid genotypes, in accordance with the assumed polyploid origin and spread linked to past glaciations, and largely independent evolution in allopatry. Conclusions: The observed spatial and genetic patterns likely reflect the evolutionary and colonization history of the two cytotypes and have been maintained by multiple factors such as ecological divergence, limited gene flow between the cytotypes, and the restricted dispersal capacity.